Inverse modeling of water retention curves in soils with different uses and coverings - Brito, Ana Flávia Cordeiro de; Teixeira, Marcella Cardoso; Oliveira, Lorene Alves de; Farias, Adriana Magalhães; Santos, Maria Ângela Cruz Macêdo dos; Amaral, Alisson Macendo (Revista de Ciências Agroveterinárias, 2025)
The soil water retention curve (CRAS) is an important hydraulic property for understanding soil water dynamics and relevant for efficient irrigation management. Inverse modeling has been widely accepted to determine CRAS due to its efficiency, especially on a large scale. The objective of this study was to determine and compare soil water retention curves through inverse modeling, in a red latosol, Cerrado phase, under different uses and soil covers. The accuracy of the curves was also evaluated using statistical indicators. For this, preserved and non-preserved samples were collected in the study areas in order to determine the structural characteristics of the soils, the physical-hydric properties and the humidity and evaporation curves, necessary to provide the Hydrus-1D model used in computational modeling. The statistical indicators coefficient of determination, mean error, root mean square error, Akaike Information Criterion and Bayesian Information Criterion demonstrated effectiveness in the modeled water retention curves. The areas of degraded Cerrado and conventional cultivation presented retention curves with higher water retention rates, compared to the organic cultivation area, result of structural changes in the systems, such as distribution and uniformity of pores. It was observed that a higher organic matter content associated with the sandy texture, in the organic cultivation area, resulted in lower water retention at low tensions (~ 348.50 kPa) sufficient to drain the water content in this system.